Temperature-responsive biodegradable injectable polymers with tissue adhesive properties. (November 2021) - Fujiwara, Soichiro; Yoshizaki, Yuta; Kuzuya, Akinori; Ohya, Yuichi
Abstract: Injectable polymers (IPs) exhibiting in situ hydrogel formation have attracted attention as vascular embolization and postoperative adhesion prevention materials. While utilizing hydrogels for such purposes, it is essential to ensure that they have appropriate and controllable tissue adhesion property, as it is crucial for them to not detach from their deposited location in the blood vessel or abdominal cavity. Additionally, it is important to maintain gel state in vivo for the desired period at such locations, where large amounts of body fluid exist. We had previously reported on a biodegradable IP system exhibiting temperature-responsive gelation and subsequent covalent cross-link formation. We had utilized triblock copolymers of aliphatic polyester and poly(ethylene glycol) (tri-PCGs) and its derivative containing acrylate group at the termini (tri-PCG-Acryl), exhibiting a longer and more controllable duration time of the gel state. In this study, the introduction of aldehyde groups by the addition of aldehyde-modified Pluronic (PL-CHO) was performed for conferring controllable and appropriate tissue adhesive properties on these IP systems. The IP systems containing PL-CHO, which were not covalently incorporated into the hydrogel network, exhibited tissue adhesive properties through Schiff base formation. The adhesion strength could be controlled by the amount of PL-CHO added. The IP system showed good vascular embolization performance and pressure resistance in the blood vessels. The IP hydrogel remained at the administration site in the abdominal space for 2 days and displayed effective adhesion prevention performance. Statement of significance: Injectable polymers (IPs), which exhibit in situ hydrogel formation, are expected to be utilized as vascular embolization and postoperative adhesion prevention materials. The tissue adhesion properties of hydrogels are important for such applications. We succeeded in conferring tissue adhesion properties onto a previously reported IP system by mixing it with Pluronic modified with aldehyde groups (PL-CHO). The aldehyde groups allowed for the formation of Schiff bases at the tissue surfaces. The tissue adhesion property could be conveniently controlled by altering the amount of PL-CHO. We revealed that the in vitro embolization properties of IPs in blood vessels could be substantially improved by mixing with PL-CHO. The IP system containing PL-CHO also exhibited good in vivo performance for postoperative adhesion prevention. Graphical abstract: Image, graphical abstract